Effects of the microRNA-99a-5p/VLDLR axis in lung cancer cell sensitivity to chemotherapy and its mechanism - Lang, Yaoguo (2023)
Lung cancer is a major cause of cancer-related death worldwide. This study investigated the regulatory effects of the microRNA-99a-5p (miR-99a-5)/VLDLR axis on lung cancer cell sensitivity to chemotherapy and its mechanism. miR-99a-5p and VLDLR expression levels were quantified using RT-qPCR and western blotting, respectively. The IC50 value of cisplatin (DDP) was determined using a CCK-8 assay. Lung cancer cell proliferation and apoptosis were measured using the CCK-8 assay and flow cytometry, respectively. The mRNA expression levels of apoptosis-related factors (Bax, Bcl-2, and Caspase-3) were evaluated using RT-qPCR. The direct relationship between miR-99a-5p and VLDLR was validated using dual-luciferase reporter gene and RIP assays. miR-99a-5p was weakly expressed in DDP-resistant lung cancer cells. Overexpression of miR-99a-5p promoted DDP sensitivity, suppressed proliferation and colony formation, and promoted apoptosis of A549/DDP cells in vitro. Mechanistically, miR-99a-5p restrained VLDLR expression by binding to VLDLR 3’UTR, and miR-99a-5p mediated inhibition of VLDLR regulated the DDP sensitivity, proliferation, and apoptosis of A549/ DDP cells. Overexpression of miR-99a-5p inhibited the growth of A549 cells and increased chemosensitivity of A549 cells to DDP in vivo. In conclusion, miR-99a-5p overexpression promotes sensitivity to DDP and cell apoptosis by downregulating VLDLR expression in A549/ DDP cells.